A Comprehensive Review of Bioequivalence Studies: Methodologies, Regulatory Considerations, and Future Directions - Liana W. Susanto (PT Dexa Medica, 2025)
Bioequivalence studies are crucial for ensuring that generic formulations meet the safety and efficacy standards established by innovator products. This review explores the fundamental concepts of bioequivalence, the commonly employed study designs, and the current statistical methodologies used for evaluation. Regulatory frameworks from major agencies (e.g., FDA, EMA, and BPOM-RI) are outlined, while challenges in study design and interpretation are examined. Furthermore, future perspectives in bioequivalence research are considered, particularly as complex drug delivery systems and personalized medicine become more prevalent. Ongoing research and evolving guidelines will continue to shape this critical area of pharmaceutical science.